Prevalence and molecular characterization of Cryptosporidium spp. in calves in the Siirt Province, Türkiye - AKYILDIZ, GÜRKAN (My University, 2023)
Cryptosporidiosis, one of the main protozoan infections of the last century, is especially dangerous for calves and causes significant economic losses. This research was carried out to determine the prevalence of Cryptosporidium spp. by microscopic and molecular methods and to determine subtypes in 100 calves up to 6 months old and with diarrhoea in the Siirt Province, Türkiye. As a result of the microscopic examination (Kinyoun’s acid-fast), Cryptosporidium spp. oocysts were found in 8 (8%) of 100 samples. As a result of nested PCR, 826-864 bp specific bands for Cryptosporidium spp. were obtained in 13 (13%) of 100 samples. When the DNA sequences of the SSU rRNA gene were compared with the NCBI Basic Local Alignment Search Tool database, it was determined that eight samples sequence analyses showed 100% similarity with the C. parvum, C. ryanae, and C. bovis samples. The detection of C. parvum, which has zoonotic importance in this study, suggests that calves with diarrhoea may be a source of contamination for other animals and humans. Therefore, animal owners and people in close contact with animals should be informed about the public health of cryptosporidiosis.
Keywords: Veteriner Bilimleri; Klinik Öncesi Bilimler; Veteriner Parazitoloji; Sağlık Bilimleri; Veterinary Sciences; Pre-Clinical Sciences; Veterinary Parasitology; Health Sciences; Tarım ve Çevre Bilimleri (AGE); Klinik Tıp (MED); Bitki ve Hayvan Bilimleri; VETERİNERLİK BİLİMLERİ; Agriculture & Environment Sciences (AGE); Clinical Medicine (MED); PLANT & ANIMAL SCIENCE; VETERINARY SCIENCES; At; Veterinerlik (çeşitli); Genel Veterinerlik; Equine; Veterinary (miscellaneous); General Veterinary